A formal test of the long-term environmental effects of road pricing in Milan. (March 2021) - Percoco, Marco
Abstract: Road pricing (the Ecopass) was introduced in Milan in January 2008 with the aim of reducing pollution. The existing literature has argued for a sizeable effect of the charge in reducing pollution in the short term, although long-term effects are less clear. This paper aims to propose a formal test of the impact of the Ecopass in the long term by using a novel methodology which combines regression discontinuity with propensity score matching. Results confirm the poor performance of the policy within 90 days to one year (depending on the pollutant) after introduction.